Phytochemical Properties and Antioxidant activity of Pollen of Typha domingensis pers. Grow in Marshes of Maysan Governorate Southern of Iraq - Ali Nazar Yaseen (Journal of Global Pharma Technology, 2019)
The aim of this study was to evaluate the antioxidant activity of the Typha domingensis Pers, naturally growing pollen in the marshes of Maysan province in southern Iraq, and to link them effectively with the total flavonoids. (75 Ethanol+75 Water) for pollen these grains contain many effective plant compounds such as tannin, glucoside, alkali, saponin, polyphenols, and flavonoids. Flavonoids were extracted from pollen and detected using thin film chromatograph technique. The amount of flavons in the extract was estimated by chromatic method with aluminum chloride and was found to be approximately 71.3 milligrams per 50 grams of pollen powder. In determining antioxidant activity, the DPPH assay was used to show that the pollen extract had a good ability to inhibit DPPH free activity by 36.21% at 250 μg / ml of flavonoids compared to standard ascorbic acid (98.01% inhibition). The research concluded that the pollen extract contains the compounds of tannins, glycosides, alkalis, sapphones, flavonoids and phenolic compounds. Total flavonoids from pollen extract showed significant antioxidant activity.Keywords: Bardy, Typha domingensis Pers., Phytochemical, Phenolics, Flavonoids.